Perception of distance learning among undergraduate medical students during COVID-19 pandemic - Desy Nofita Sari; Rizkia Chairani Asri; Zurraya Fadila (Intelektual Pustaka Media Utama, 2023)
In response to the newly emerging coronavirus disease or COVID-19 pandemic and its profound consequences on the world, many changes have been made to medical education. It includes teaching and learning methods that ensure the educational process’s success. The Andalas University Faculty of Medicine, Indonesia had to implement new online teaching strategies. This study examined how medical students perceived online education during the COVID-19 outbreak. The study is cross-sectional, employed online questionnaires. The response was that most students prefer face-to-face learning in practicum and clinical skills, which require hands-on methods to improve student skills. Half the students were satisfied, and several were neutral about distance learning. The student who agrees that the lecturer is active and has the expertise and knowledge for the class is more satisfied with distance learning (p0.001). The student who agrees about the platform quality, understandable learning guide, and facility from faculty has a higher level of satisfaction with distance learning (p0.001). This study concluded that a medical student at the Andalas University Faculty of Medicine was mainly satisfied with the institution’s response to the pandemic. However, medical faculty must evaluate and improve the quality of education in online learning.